PENGEMBANGAN MODUL BRYOPHYTA BERBASIS HASIL PENELITIAN DI TAHURA NGARGOYOSO KARANGANYAR UNTUK SISWA KELAS X SMA - Acna Clara Aida Wati; Tri Wiharti; Anwari Adi Nugroho (Florea : Jurnal Biologi dan Pembelajarannya, 2019)
The purpose of this study was to 1) determine the characteristics of the module based on the identification of Bryophyta in Ngargoyoso Karanganyar Forest Park for grade X students of high school; 2) determine the feasibility of modules based on the identification of Bryophyta (Moss Plant) in Ngargoyoso Karanganyar Forest Park in terms of material aspects, aspects of module presentation, biology teachers and students. This type of research is research and developer according to Brog and Gall which was modified into 7 stages, among others is 1) research and information gathering; 2) planning; 3) initial product development; 4) trial of initial product; 5) initial product revision; 6) limited field testing; 7) second product revision. The results of this study indicate that there were studi 13 species of Bryophyta that can be used for the development of biological modules with Bryophyta material. Material expert assessment was obtained 81.89% so that it was included in the feasible category with very good qualifications, module expert judgment was obtained 83.62% so that it was included in the decent category with very good qualifications, the average assessment of practitioners of biology teachers was obtained 83.40% so it included in the feasible category with very good qualifications, and the percentage of user assessment of Grade X MIPA students was obtained 85.53% so that it was included in the decent category with very good qualifications. Based on this, it can be concluded that the biology module developed was included in the feasible category with very good qualifications and can be continued in operational tests.